The Javanese Cultural Values in Lengger Giyanti Mask, Wonosobo - Eko Budiyanto, Ari Eko Budiyanto Ari; Triyanto, Triyanto; Ibnan Syarif, Muh. (Universitas Negeri Semarang, 2019)
Lengger Giyanti Mask Art Wonosobo is a popular traditional art that is full of noble cultural values ​​that exist in the lives of its people. Art that develops in the communities around the Dieng mountains is inseparable from spiritual and religious values, whose teachings are conveyed in the form of Javanese community symbols. The purpose of this research is to analyze the Javanese cultural values ​​that exist in Wonosobo's Lengger Giyanti Mask. This study uses a type of qualitative research. Data collection techniques are carried out by interviews, direct observation and document study. The collected data is then analyzed inductively through the stages of reduction, data presentation, and verification.The results showed that the Lengger Giyanti Mask show, Wonosobo Regency always gave rise to Javanese cultural values. Cultural values ​​expressed in Mask Lengger in Giyanti Village, Wonosobo Regency generally have cultural values, namely values ​​about norms or rules while in values ​​related to Javanese culture are divided into 3 namely (1) cosmologically, contained in Sulasih mask dance, which invites gods and goddesses and ancestors to come to the performance; (2) in symbolic classification, each mask has a representation of basic human characteristics; and (3) in the orientation of the life of the Javanese people, in the mask art of Lengger there are symbols or implied messages, namely dance pangeling or reminder (advice).